2013
DOI: 10.4103/1793-5482.116389
|View full text |Cite
|
Sign up to set email alerts
|

Interference of apoptosis in the pathophysiology of subarachnoid hemorrhage

Abstract: Programmed cell death is crucial for the correct development of the organism and the clearance of harmful cells like tumor cells or autoreactive immune cells. Apoptosis is initiated by the activation of cell death receptors and in most cases it is associated with the activation of the cysteine proteases, which lead to apoptotic cell death. Cells shrink, chromatin clumps and forms a large, sharply demarcated, crescent-shaped or round mass; the nucleus condenses, apoptotic bodies are formed and eventually dead c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 65 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…A large body of evidence demonstrates that inflammation appears to be the proegumenal cause of brain injury after SAH [ 32 ] and that patients with high levels of cytokines (such as IL-1β and TNF-α) would have unfavorable outcomes and symptoms for clinical deterioration [ 33 ]. Inflammation induces apoptosis [ 34 ] and leads to BBB disruption by increasing endothelial permeability and vessel diameter [ 35 ]. In addition, a number of studies have indicated the critical role of neutrophils in the inflammatory response [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of evidence demonstrates that inflammation appears to be the proegumenal cause of brain injury after SAH [ 32 ] and that patients with high levels of cytokines (such as IL-1β and TNF-α) would have unfavorable outcomes and symptoms for clinical deterioration [ 33 ]. Inflammation induces apoptosis [ 34 ] and leads to BBB disruption by increasing endothelial permeability and vessel diameter [ 35 ]. In addition, a number of studies have indicated the critical role of neutrophils in the inflammatory response [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PGRN modulates neutrophilic inflammation by inhibiting the activation and recruitment. However, activated neutrophils can secrete neutrophil elastase (NE) to degrade PGRN into individual granulin peptides, which act in the opposite manner, stimulating the production of pro-inflammatory cytokines [ 17 , 34 ]. Therefore, we hypothesized that a decrease in PGRN levels potentiates the inflammation induced by EBI and that high levels of PGRN may inhibit inflammation by suppressing neutrophil activation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that Zileuton significantly upregulated levels of activated (phosphorylated) Akt after SAH while decreasing NF-κB, LTB4, TNF-α, IL-6 and IL-1β. Activated Akt inhibits pro-apoptosis proteins such as Bax and promotes anti-apoptotic proteins such as Bcl-2 [ 31 ]. At the same time, Zileuton could reduced cerebral edema and prevented BBB disruption and attenuated the neurological deficits.…”
Section: Discussionmentioning
confidence: 99%
“…There are several molecules within the apoptotic cascade that could be targeted for neuroprotection after SAH, for example, active caspases, p53, the mitochondrial membrane and death receptors [ 69 , 70 ]. We will describe a selection of strategies aimed at reducing apoptosis at various levels of the cascade below.…”
Section: Introductionmentioning
confidence: 99%